Using Rainbow of Films to Teach Educational Psychology - Helaiya, Sheetal (Voices of Teachers and Teacher Educators, 2019)
Teacher Education acts in a direction that helps to achieve objective of human resource development. Kothari Commission (1964-66) correctly said that “The destiny of India is now being shaped in her class.” Education plays an important role not only in building personality of a child, but also in shaping the society. So, it is essential that teaching learning process be around the life of an individual and for this purpose, teacher has to make use of resources available in the society. Presently, youth is more close to social media and entertainment industry. The youth adopts many things from such media sources. Teacher can make use of it as one of the resources in films to teach educational psychology to student-teachers. The experiment was carried out on student teachers of IITE and it was found that they were able to relate themselves with clips of movies. The study found that student teachers felt that their way of thinking had changed and they started analysing situation and behaviour of the individual with different angle.